Production of Exopolysaccharides Through Fermentation of Secondary Whey with Kefir Grains - Aidalú Hernández-Martínez; Carlos Jiménez-Pérez; Alma Cruz-Guerrero; John F. Trant; Sergio Alatorre-Santamaría (Biology and Life Sciences Forum, 2025)
The cheese industry produces millions of tons of lactose-rich whey yearly, of which 50% is discharged into water and soil, leading to significant environmental challenges. In Mexico, cheese whey is repurposed for traditional cheese production. However, another by-product named secondary whey (SW) remains. This study focused on the production of exopolysaccharides (EPSs) via SW fermentation of kefir grains, yielding 632.6 ± 30.8 mg/L of a freeze-dried solid, and the carbohydrate-to-protein ratio stood at 2.89, corresponding to the bound EPS protein content. Through the analysis of Fourier Transform Infrared Spectroscopy (FTIR) spectra, it was determined that EPSs were successfully produced, as a signal was observed between 1200 and 1000 cm−1, characteristic of the glycosidic bonds in polysaccharides.